1, 3-Dibromo-5, 5-dimethylhydantoin (DBDMH)-promoted cross-coupling of enaminones with phenols under metal-free conditions. (28th September 2022) - Duan, Xiaoge; Liu, Kun; Meng, Zhen; Guo, Yufei; Li, Hui; Liu, Ning; Qu, Wanting; Duan, Xiyan; Ma, Junying
Graphical abstract: Abstract: Despite significant progress in the area of enaminone vinyl CH functionalization, approaches for the direct synthesis of phenoxyl enaminone molecules remain a challenge. Here we describe a highly efficient 1, 3‑Dibromo 5, 5-dimethylhydantoin (DBDMH)-promoted cross-coupling reaction between enaminones and phenols. This method provides straightforward access to a wide range of polyfunctionalized aminophenoxyalkenes under mild conditions. The main advantageous features of this method includes a wide substrate scope and good functional group tolerance, operational simplicity, and easily available starting materials.